ANALISIS PENGEMBANGAN USAHA BUDIDAYA IKAN LELE (Clarias sp) DI KOTA KUPANG - Joi A. Surbakti; Naharuddin Sri; Alexander S. Tanody (Politeknik Pertanian Negeri Kupang, 2018)
Economic analysis of the business development catfish farming in Kota Kupang aims to: feasibility mengetetahui catfish farming comprising: aspects of market , technical , financial , management, institutional involved , the law ( kelegalan effort ) , socio-economic and environmental aspects, recognize the catfish farming business development and Plan out effort (Business Plans ) cultured catfish .This research used descriptive method . Descriptive method is a method which aims to provide a general, systematic , factual and actual . This descriptive method are two: the descriptive method qualitative and quantitative methods . Implementation of current research in the field is to survey techniques that emphasize the historical data in the bibliography. Sampling techniques / determination of respondents do purposive sampling studies where samples are selected based on judgment . While the considerations taken based on the purpose of the study. Requirements Analysis Investment Business by knowing some aspects of which are: Aspects of the market, Technical Aspects , investment aspect and Aspects of management.